Antidepressive effects of a chemically characterized maqui berry extract (Aristotelia chilensis (molina) stuntz) in a mouse model of Post-stroke depression. (July 2019) - Di Lorenzo, Arianna; Sobolev, Anatoly P.; Nabavi, Seyed Fazel; Sureda, Antoni; Moghaddam, Akbar Hajizadeh; Khanjani, Sedigheh; Di Giovanni, Carmen; Xiao, Jianbo; Shirooie, Samira; Tsetegho Sokeng, Arold Jorel; Baldi, Alessandra; Mannina, Luisa; et al.
Abstract: Mood disorders occur in 30% of stroke patients, and of these post-stroke depression (PSD) is the most significant. This study aimed to evaluate the antidepressive-like effects and in vivo antioxidant activity of a chemically characterized maqui berry ( Aristotelia chilensis (Molina) Stuntz) extract obtained from an optimized extraction method, on a murine PSD model. The extraction process was optimized to maximize anthocyanin content, and the phytochemical profile of the extract was evaluated using a multi-methodological approach including a liquid chromatographic method coupled with mass spectrometry and nuclear magnetic resonance spectroscopy. The antidepressive-like activity was investigated through despair swimming and tail suspension tests. The in vivo antioxidant activity was evaluated in mouse brain tissue by measuring the activity of antioxidant enzymes and lipid peroxidation products. A number of compounds have been first identified in maqui berry here, including malvidin-glucoside, GABA, choline and trigonelline. Moreover, the results showed that the antidepressive-like activity exerted by the extract, which was found to restore normal mouse behavior in both despair swimming and tail suspension tests, could be linked to its antioxidant activity, leading to the conclusion that maqui berries might be useful for supporting pharmacological therapy of PSD by modulating oxidative stress. Graphical abstract: Image 1 Highlights: Phytochemical characterization of maqui ( Aristoteilia chilensis ) extract. Influence of maqui berry extract on post-stroke depression mouse model system. In vivo antioxidant activity in mouse brain exerted by maqui berry extract.